2011
DOI: 10.1111/j.1751-7893.2011.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic experience subtypes, poor mental health status and help‐seeking behaviour in a community sample of young adults

Abstract: PEs subtypes are differentially associated with various markers of poor mental health status. PI seem to have stronger psychopathological significance than other subtypes of PEs. Further longitudinal studies are required to extend these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Earlier studies on an adolescent UHR (Cornblatt et al, 2007) and a mixed-age help-seeking sample (Yung et al, 2006) had also reported 'suspiciousness/persecutory ideas' as the most frequent clinician-assessed APS, and the factor 'Conceptual Disorganization and Suspiciousness' was most frequent in questionnaire-studies (Armando et al, 2010(Armando et al, , 2012(Armando et al, , 2013Brandizzi et al, 2014).…”
Section: Attenuated Psychotic Symptoms and Development Of Psychosismentioning
confidence: 99%
“…Earlier studies on an adolescent UHR (Cornblatt et al, 2007) and a mixed-age help-seeking sample (Yung et al, 2006) had also reported 'suspiciousness/persecutory ideas' as the most frequent clinician-assessed APS, and the factor 'Conceptual Disorganization and Suspiciousness' was most frequent in questionnaire-studies (Armando et al, 2010(Armando et al, , 2012(Armando et al, , 2013Brandizzi et al, 2014).…”
Section: Attenuated Psychotic Symptoms and Development Of Psychosismentioning
confidence: 99%
“…41,42 In determining the number of factors to retain, 4 studies reported the use of eigenvalues and scree test, Monte Carlo simulations or a combination. [40][41][42]45 Three studies failed to report their determination criteria. None of the EFA studies were followed up by CFA to confirm their results.…”
Section: Factor Structure Of the Positive Domain Of Capementioning
confidence: 99%
“…Validation studies on translations of CAPE included Spanish, 39,43 French, 36,38 Italian, 42 Greek, 44 and Swedish.…”
Section: Languagementioning
confidence: 99%
“…However, the low transition rates and the fact that most CHR individuals suffered from mood and anxiety disorders suggest that FRS should not only be considered markers for psychotic disorders but also for a wider range of mental disorders, which may present with psychotic experiences that may not evolve to frank psychotic disorders [4,27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent longitudinal studies among individuals at CHR have reported transition rates to full-blown psychosis of between 7 and 54% [3]. While the clinical signs and symptoms among individuals at CHR have been widely studied at a dimensional level [4,5,6], few studies have evaluated possible qualitative aspects of positive psychotic symptoms that might predict poorer outcomes and/or conversion to psychosis [4]. …”
Section: Introductionmentioning
confidence: 99%